Numerical investigation on the hydrodynamic characteristics of an autonomous underwater glider with different wing layouts - Javaid, M.Y. (Asian Research Publishing Network, 2017)
An autonomous underwater glider is a self-propelled underwater vehicle which is designed primarily for oceanography. It moves with low speed in saw-tooth pattern and has long endurance. The vertical motion of the glider is controlled by changing its buoyancy and its wings convert this vertical motion into horizontal motion. The hydrodynamic coefficients of glider will dictate its performance and possible applications. In this paper, the impact of rectangular and tapered wings on the hydrodynamics coefficient of a glider and the corresponding glide velocity was investigated using ANSYS Computational Fluid Dynamics (CFD) turbulence model and FLUENT flow solver. The lift force of a rectangular wing is higher with less drag force compared to tapered wings. A glider with tapered wings glider will have a larger glide angle and is therefore suitable of deep ocean applications. © 2006-2017 Asian Research Publishing Network (ARPN).